2021
DOI: 10.1002/csc2.20437
|View full text |Cite
|
Sign up to set email alerts
|

Colonial bentgrass transcript‐expression differences compared with creeping bentgrass in response to water‐deficit stress

Abstract: Natural stands of creeping bentgrass (Agrostis stolonifera) are often found in wetland areas and exhibit very poor tolerance to dry soils. Colonial bentgrass (A. capillaris) is frequently found in drier habitats and has the ability to go dormant and recover quickly under water‐deficit stress. Hybridization between creeping and colonial bentgrass is possible and a better understanding of gene regulation under water‐deficit conditions of the two species could improve breeding strategies for water deficit–toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Transgenic plants overexpressing transcription factors, ion transport channels, osmoprotectants, stress-signaling genes, and maintaining osmotic balance were found to impart stress tolerance [54]. RNA-seq based transcriptome analysis in different turfgrass species revealed that genes underlying ROS, transcription factors, hormones, carbohydrate metabolisms, and protein phosphorylation and ubiquitination, were largely enriched in stressed plants [55,56]. Therefore, drought stress tolerance in turfgrass can be enriched through genetic manipulation for these genes.…”
Section: Genetic Manipulation For Enhanced Drought Stress Tolerancementioning
confidence: 99%
“…Transgenic plants overexpressing transcription factors, ion transport channels, osmoprotectants, stress-signaling genes, and maintaining osmotic balance were found to impart stress tolerance [54]. RNA-seq based transcriptome analysis in different turfgrass species revealed that genes underlying ROS, transcription factors, hormones, carbohydrate metabolisms, and protein phosphorylation and ubiquitination, were largely enriched in stressed plants [55,56]. Therefore, drought stress tolerance in turfgrass can be enriched through genetic manipulation for these genes.…”
Section: Genetic Manipulation For Enhanced Drought Stress Tolerancementioning
confidence: 99%
“…This article is a U.S. Government work and is in the public domain in the USA. (Amundsen et al, 2020). Creeping bentgrass (Agrostis stolonifera L. 2n = 4x = 28) is a fine textured grass that can tolerate extremely low mowing heights and is widely utilized on golf courses where cool-season grasses are adapted (Warnke, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Colonial bentgrass ( Agrostis capillaris L. 2 n = 4 x = 28) is a turfgrass species that can be established on grass tennis courts, golf course fairways, and used for erosion control (Ruemmele, 2003). In addition, colonial bentgrasses exhibit considerably better resistance to the important fungal disease dollar spot caused by several species in the new genus Clarireedia (Salgado‐Salazar et al., 2018) and have shown improved water‐deficit stress tolerance (Amundsen et al., 2020). Creeping bentgrass ( Agrostis stolonifera L. 2 n = 4 x = 28) is a fine textured grass that can tolerate extremely low mowing heights and is widely utilized on golf courses where cool‐season grasses are adapted (Warnke, 2003).…”
Section: Introductionmentioning
confidence: 99%